A New Theoretical Platform of Personality Development in the System of Higher Education - Berulava, Galina A.; Berulava, Mikhail N. (International Dialogues on Education Journal, 2019)
The article discusses the main factors of personal development and the dynamics of their role in the modern world. It is shown that an organized system of education, a teacher, is no longer a priority source of personal development: such a source is the electronic media that are today having a mostly negative impact on personal development. The paper considers the prognosis of the new trends in personality development: decentralization of the universities functioning; identification as the main source of personal development via electronic information sources; development, active use of educational films and video courses, the formation of positive stereotypes of mental activity in the individual. It is substantiated that the answer to the question of what and how to teach in a higher education institution autonomously is impossible, without analyzing the role of various sources of personality development and, in particular, a detailed philosophical, sociological, and psychological analysis of the role of modern electronic means for the formation of personality.